Indonesian-English Code Mixing Found in Wardah Beauty Youtube Channel - Ni Nyoman Niki Tresna Sari; I Komang Sulatra; Ni Wayan Suastini (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study deals with the analysis of code mixing phenomenon found in Wardah Beauty YouTube channel on a special episode called Heart to Heart with Dewi Sandra. This study aims to identify the types and reasons of code mixing found in Wardah Beauty YouTube channel. The theory from Hoffman (1991) is applied to analyze the data. In achieving the objectives, the descriptive qualitative method is used to analyze the data. In collecting the data, this study uses observation and note-taking techniques. The data were taken from the Wardah Beauty YouTube channel videos from August 2019 to May 2021. Meanwhile, the informal method was used to presenting the data. The dominant type found in this study is intra-sentential, and the lowest occurrence was obtained by involving a change of pronunciation. Meanwhile, talking about a particular topic becomes the dominant reason of code mixing found in this study.